#TITLE_ALTERNATIVE# - RETNOSARI (NIM : 20512005) ; Pembimbing Prof. Dr. Euis Holisotan Hakim, Dr. Rukman Hertadi, RINI
Phytochemical studies showed that Morus plants produce some prenylated phenolic compounds, such as stilbenoids, 2-arylbenzofurans, flavonoids, and adduct Diels-Alder. Bioactivities of those compounds were higher compared to non prenylated ones, thereby isoprenyl group addition is critical for the bioactivity. Artocarpine, for instance, exhibited stronger cytotoxic activity against murine leukemia P-388 cells than norartocarpetine that lack of isoprenyl group. In this work, we performed the preliminary study to an enzyme responsible for the prenylation process, namely prenyltransferase, which was from isolated from leaves and stem bark of M. macroura. Crude enzyme was prepared by homogenization and fractionation with 20% ammonium sulfate. Crude enzyme derived from homogenization and amonium sulphate fractionation of leaves were labeled as ED and AD, respectively. While EK and AK labels were given for the crude enzymes obtained from homogenation and ammonium sulfate fractionation of stem bark. Prenyltransferase activity was measured by incubating the mixture of each crude enzymes, norartocarpetine (non prenylated flavone) and dimethylallyl pyrophosphate (DMAPP) as a prenyl donor for 24 hours in 30oC. The reaction product was quantified and identified using HPLC and LC-MS after they were extracted using ethyl acetate. HPLC result using reverse phase C18 column for ED and AD gave chromatogram’s peak at the retention time of 1,4 minutes for substrate and 4,3 minutes for product. The reaction product were further elucidated by LC-MS and found m/z value of (M-H)- around 421,1546, which corresponds to the molecular weight of norartocarpetin owing two isoprenyl group. In case for EK, HPLC analysis using the same column found the chromatogram’s peak at retention time of 1,4 minutes and 2,1 minutes for substrate and product, respectively. LC-MS result for the reaction product gave m/z value of M-H+ around 457,2150 which is the expected mass for norartocarpetine with two isoprenyl group and two hydroxyl group. When the enzymatic reaction was shorten up to 8 hours, however, the reaction product became norartocarpetine with two isoprenyl group and one hydroxyl group with m/z value of iv M-H+ about 437,2063. Based on these result, crude enzyme from stem bark of M. macroura contained active prenyltransferase and hydroxilase.